Polyarylate based thin film composite (TFC) membranes: effects of coating parameters, gutter layer, and intrinsic material properties - Chendake, Yogesh J.; Bhole, Yogesh S.; Lohokare, Harshada R.; Kharul, Ulhas K. (Separation Science and Technology, 2010)
Investigations in thin film composite (TFC) membrane formation with polyacrylonitrile ultrafiltration membrane as a support and three polyarylates with sequentially increased polarity are reported. Effects of TFC membrane preparation parameters viz., concentration of the coating solution, dip time, presence of solvent in pores of UF membrane support, and presence of the gutter layer were examined towards the formation of the selective skin layer, which was assessed by gas permeation analysis. TFC membranes prepared using dimethyl bisphenol-A based polyarylate exhibited similar to 3 orders of magnitude higher permeability and comparable selectivity as that of its dense membrane.
Keywords: Gas permeation; gutter layer; polarity; polyarylates; TFC membrane